Affective Trust in Chinese Leaders - Chen, Xiao-Ping; Eberly, Marion B.; Chiang, Ting-Ju; Farh, Jiing-Lih; Cheng, Bor-Shiuan (Journal of Management, 2014)
Adopting the theoretical framework of social exchange, the authors used the two dominant Confucian values—hierarchy and relationalism—to theorize the mediating role of affective trust in the relationship between paternalistic leadership and employee in-role and extra-role performance in the Chinese organizational context. Data from 601 supervisor–subordinate dyads of 27 companies in a Taiwanese conglomerate revealed that while the benevolence and morality dimensions of paternalistic leadership are positively associated with both in-role and extra-role performance, the authoritarian paternalistic leadership dimension is negatively related to subordinate performance. Furthermore, affective trust mediated the relationship between benevolent and moral paternalistic leadership and employee performance but did not mediate the relationship between authoritarianism and employee performance. The theoretical and practical implications of these findings are discussed in the Chinese context and beyond.